Testicular Blood Flow: A Review of Hemodynamics, Thermoregulation and Clinical Applications in Domestic Animals - Kumar, Sushil; Srivastava, Neeraj; Lakhanpal , Divyanshu (The Indian Journal of Animal Reproduction, 2025)
In species propagation, males play a crucial role, making testicular hemodynamic—referring to blood flow within the testicles—an essential parameter for evaluating fertility. It’s important for testicular function, including sperm production and steroid production for behavioural response of the males. This article reviews testicular hemodynamic, along with the various tools to study it and to improve testicular blood flow with their clinical significance. The highly convoluted testicular artery, particularly prominent in farm animals like bulls and rams, facilitates heat dissipation, crucial for main taining the lower body-temperature crucial for spermatogenesis. Testicular blood perfusion (TBP) is vital for nutrient and hormone exchange and thermoregulation, achieved through vascular mechanisms (pampiniform plexus, superficial vessels) and non-vascular mechanisms (sweating, cremaster muscle, tunica dartos muscle). Colour Doppler ultrasonog raphy (CDU) is a valuable non-invasive tool for assessing TBP, measuring parameters like peak systolic velocity (PSV), resistive index (RI), and plasticity index (PI). Several factors viz., environmental (temperature, season), physiological (species, breed, age, sexual activity, disease), and technical (Doppler technique, transducer type, operator experience) factors influence TBF. The article explores methods to improve TBP in farm animals, such as GnRH/hCG administration, passive inhibin immunization, and melatonin or selenium-enriched probiotic supplementation.